Epidemiological profile and study on waiting lists for corneal transplants in a tertiary hospital - Bittencourt, Jacqueline Lunardelli; Gatti, Ítala de Mores Vieira; Lessa, Carolina Falcão; Cirillo, Luciano Rabello Netto; Ierardi, Mariana Gameiro; Garcia, Marina Paulino; Martins, Luiz Antônio de Brito; Fonseca, Fernando Luiz Affonso; Lima, Vagner Loduca (ABCS Health Sciences, 2020)
Introduction: Epidemiological studies and about patients’ waiting time on queues for corneal transplantation are important, as they allow us to know the assisted population and assist the medical team. Objective: To evaluate the epidemiological and demographic profile of patients undergoing corneal transplantation from January 2014 to September 2018 at a teaching hospital in the city of Santo André, as well as their waiting time for the procedure. Methods: Retrospective descriptive study, performed through analysis of medical records and data from the website of the Government of the State of São Paulo’s transplant center. The study was conducted at the External and Corneal Diseases sector of the discipline of Ophthalmology from Centro Universitário FMABC. The following data were evaluated: gender, age, race, origin and waiting time for the patient to have a transplant. Results: A total of 139 corneal transplant patients were recruited for the study, with a mean age of 47.4±23 years. According to gender, just over half of the transplanted were female (50.4%). Regarding to skin color, 45.3% of the patients were white, 44.6% were brown and 10.1% were black. As for their origin, most patients were from the city of Santo André. Conclusion: This study enabled the assessment and knowledge of the epidemiological profile and waiting time for corneal transplantation in our patients. This information is important, as it helps us to understand the profile of the assisted population and in the organization and planning of the medical team, contributing to better guidance and care for the patients.